Band and bonding characteristics of N2+ ion-doped graphene. Issue 88 (7th September 2016) - Park, Heemin; Choi, Seongsoo; Lee, Paengro; Kim, Jingul; Ryu, Mintae; Kim, Kwang S.; Chung, Jinwook
Abstract : We report that the doping of energetic nitrogen cations (N2 + ) on graphene effectively controls the local N–C bonding structures and the π-band of graphene critically depending on ion energy E k (100 eV ≤ E k ≤ 500 eV). Abstract : We report that the doping of energetic nitrogen cations (N2 + ) on graphene effectively controls the local N–C bonding structures and the π-band of graphene critically depending on ion energy E k (100 eV ≤ E k ≤ 500 eV) by using a combined study of photoemission spectroscopy and density functional theory (DFT) calculations. With increasing E k, we find a phase transformation of the N–C bonding structures from a graphitic phase where nitrogen substitutes carbon to a pyridinic phase where nitrogen loses one of its bonding arms, with a critical energy E ck = 100 eV that separates the two phases. The N2 + -induced changes in the π-band with varying E k indicate an n-doping effect in the graphitic phase for E k < E ck but a p-doping effect for the pyridinic graphene for E k > E ck. We further show that one may control the electron charge density of graphene by two orders of magnitude by varying E k of N2 + ions within the energy range adopted. Our DFT-based band calculations reproduce the distinct doping effects observed in the π-band of the N2 + -doped graphene and provide an orbital origin of the different doping types. We thus demonstrate that the doping type and electron number density in the N2 + ion-doped SLG can be artificially fine-controlled by adjusting the kinetic energy of incoming N2 + ions.